P0274A NOVEL METHOD FOR THE ASSESSMENT OF RENAL BIOPSY WITH THE ACTIVATABLE FLUORESCENT PROBE. (6th June 2020) - Iyama, Takuji; Takata, Tomoaki; Mae, Yukari; Taniguchi, Sosuke; Ida, Ayami; Ogawa, Masaya; Yamamoto, Marie; Fukuda, Satoko; Isomoto, Hajime
Abstract: Background and Aims: Renal biopsy is one of the most important procedures in nephrology. The histological analysis of biopsy tissues is important for the diagnosis and prognosis assessment of renal diseases, as well as determining the treatment strategy. It is necessary to obtain biopsy specimens containing renal cortex for such purpose. Although renal biopsy is the undisputed diagnostic procedure, there always is a need to weigh the benefits against the potential complications. A novel activatable fluorescent probe that reacts with a peptide, which is highly expressed in the renal cortex, has been developed. We evaluated the feasibility of this probe for assessing renal biopsy specimens. Method: The fluorescent probe was firstly applied to renal proximal tubular cells in order to evaluate the fluorescent emission. Then the probe was applied to mouse kidneys ex vivo . Finally, it was applied to human biopsy specimens (n=12). Fluorescent images were acquired using commercially available digital camera equipped with optical interference filter. Fluorescent intensities were quantified and the intensities in cortex and medulla were compared. Results: We observed fluorescent emission from the renal proximal tubular cells immediately after the administration of the fluorescent probe. The fluorescent intensity gradually increased with time. The fluorescence signal was detected in the mouse kidneys ex vivo without markedly affecting the tissue morphology. The probe on human biopsy specimens also emitted fluorescent and the fluorescent could be detected in all the patients examined. In addition, the cortico-medullary junction could be identified in the fluorescent image (Figure). The fluorescent intensities in renal cortex were remarkably stronger than in medulla. Conclusion: Renal biopsy specimens can be assessed by fluorescent image using this activatable fluorescent probe. This novel fluorescent probe is useful in clinical nephrology.